Strategi dan Pendekatan Pengelolaan Kelas (International Forum of Researchers and Lecturers, 2025)
This study examines various proactive and reactive classroom management strategies and approaches to create a conducive learning environment. Effective classroom management is crucial for minimizing disruptions, enhancing student engagement, and supporting their academic and socio-emotional development. The literature review covers preventive measures such as establishing clear expectations and routines, building positive teacher-student relationships, and creating physically and emotionally safe learning spaces. Additionally, reactive strategies for addressing disruptive behaviors—including verbal and non-verbal interventions, conflict resolution, and de-escalation techniques—are discussed. The study emphasizes the importance of consistent, fair, and culturally responsive approaches tailored to student diversity and needs. The analysis reveals that the effectiveness of approaches such as authoritative, democratic, and behavioral modification varies depending on the context, with recommendations to flexibly combine multiple methods. Challenges like student heterogeneity, limited facilities, and teacher preparedness are identified, along with innovative solutions such as differentiated instruction and technology integration.